Thinking Beyond Acute Kidney Injury - Emran El-Alali; Cesar Moreno; Emad Al Jaber (Case Reports in Nephrology and Dialysis, 2022)
Acute kidney injury (AKI) can be a significant clue to solving a puzzling patient presentation. Postrenal AKI should be suspected if imaging shows any degree of hydronephrosis and can be caused by a variety of conditions. Diagnosis of urinary obstruction without significant dilatation of the pelvic-ureteral system requires a higher degree of suspicion, and hence, its identification can become late. In patients without prior cancer screening, the etiology of obstructive uropathy must be broadened to include primary or metastatic malignancy. Clinicians should look beyond the AKI to properly evaluate the etiology of the patient’s presentation and symptoms. In this report, we present the case of a middle-aged female with no known past medical history who presented with AKI secondary to malignant retroperitoneal fibrosis as the first manifestation of metastatic breast cancer. Her AKI was associated with acute onset anuria and was found to have nondilated postrenal AKI with no significant abnormalities on renal imaging. Early onset anuria in the setting of AKI, which persists despite fluid resuscitation, can suggest complete urinary tract obstruction even with reassuring results of initial renal images, and in the patient with no history of cancer screening, malignancy should be suspected as a primary cause of obstructive uropathy.